Marine Conservation in the Azores: Evaluating Marine Protected Area Development in a Remote Island Context - Abecasis, Rita C.; Afonso, Pedro; Colaço, Ana; Longnecker, Nancy; Clifton, Julian; Schmidt, Luisa; Santos, Ricardo S. (Frontiers in Marine Science, 2015)
In the Archipelago of the Azores, over 110,000 km2 of marine areas presently benefit from some form of protection, including a suite of coastal habitats, offshore areas, seamounts, hydrothermal vents and large parcels of mid-ocean ridge. These areas are integrated in the recently established network of marine protected areas (MPAs), which stands as the cornerstone of Azorean marine conservation policies. This article describes and analyses the process of MPA establishment in the Azores and the current network of protected areas. Three phases of MPA development are identified, progressing from individual MPA establishment with little scientific support in the 1980s, the increasing scope of scientific research during the 1990s under European Union initiatives and the gradual implementation of an MPA network in the 2000s. Expert critical evaluation of the contemporary situation demonstrates that this network must be integrated within a wider regional marine management strategy, with MPA success being contingent upon the implementation of management plans, appropriate enforcement and monitoring, and bridging gaps in scientific knowledge.